Immobilization of Heavy Metals Using Biochar and Manganese Dioxide for Preventing Pollution - Shui-Wen Chang Chien; Pei-Qi Lu (Engineering Proceedings, 2025)
Using biochar/δ-MnO2 as an adsorbent, heavy metals in soil were immobilized to prevent further pollution. When biochar/δ-MnO2 was thoroughly mixed with contaminated soil in a ratio of 2:8, the residual fractions of As, Cu, Pb, and Zn increased by 9.78, 39.0, 61.6, and 15.7%. The addition of biochar/δ-MnO2 significantly immobilized Cu and Pb. Since biochar/δ-MnO2 fixed As, Cu, Pb, and Zn in the soil, soil contamination was prevented effectively.